2013
DOI: 10.1111/clr.12146
|View full text |Cite
|
Sign up to set email alerts
|

Osteoblastic and osteoclastic differentiation on SLA and hydrophilic modified SLA titanium surfaces

Abstract: It may be concluded that the modSLA surface promotes osteogenic effect and prevents osteoclastic differentiation. Promotion of osteoblastic proliferation after a short-term cell culture might be responsible for stimulated bone regeneration implying that early loading may be possible. Also, the anti-osteoclastic effect of the modSLA surface may contribute to maintenance of the marginal bone level of dental implants, implying long-term stability would be provided by this surface technology. The modSLA surface ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 27 publications
(44 reference statements)
0
56
0
2
Order By: Relevance
“…Though, after 7 days of seeding, the authors demonstrated a signifi cantly increased OPG gene expression and a significantly decreased RANKL gene expression on modSLA surfaces in comparison to SLA surfaces [ 117 ]. In addition to that, mouse bone marrowderived macrophages showed a signifi cantly reduced gene expression of osteoclastogenesisrelated genes (TRAP, NFATc1, OSCAR, c-Fos) on modSLA surfaces compared to SLA surfaces [ 127 ]. Mature dendritic cells can also initiate T-cell activation and therefore infl uence the differentiation of osteoclasts [ 131 ].…”
Section: Modsla: Bone Tissue Healing and Remodelingmentioning
confidence: 86%
“…Though, after 7 days of seeding, the authors demonstrated a signifi cantly increased OPG gene expression and a significantly decreased RANKL gene expression on modSLA surfaces in comparison to SLA surfaces [ 117 ]. In addition to that, mouse bone marrowderived macrophages showed a signifi cantly reduced gene expression of osteoclastogenesisrelated genes (TRAP, NFATc1, OSCAR, c-Fos) on modSLA surfaces compared to SLA surfaces [ 127 ]. Mature dendritic cells can also initiate T-cell activation and therefore infl uence the differentiation of osteoclasts [ 131 ].…”
Section: Modsla: Bone Tissue Healing and Remodelingmentioning
confidence: 86%
“…The increased surface roughness was found to facilitate the adhesion of biomacromolecules and cells. 24 Together with surface roughness, surface wettability is an important factor influencing osteoblast cell responses to implant surfaces. It has been confirmed that an increased International Journal of Nanomedicine 2014:9 submit your manuscript | www.dovepress.com…”
Section: Discussionmentioning
confidence: 99%
“…More interesting is the hydrophilic behavior of the chemically treated surface, considering that high wettability of the implant by the physiological fluids is believed to facilitate protein adsorption, formation and link of the fibrin clot and cell attachment [71]. Differentiation of osteoblasts was significantly increased on less hydrophobic surfaces, as supported also by RT-PCR evaluation for the expression of Runx2, OPN, and OCN [72].…”
Section: Surface Wettabilitymentioning
confidence: 90%